PO228 The clinical features and prognosis of scan negative uro-neurological disorders. (1st December 2017) - Hoeritzauer, Ingrid; Panicker, Jalesh; Granitsiotis, Voula; Elneil-Coker, Sohier; Demetriades, Andreas; Statham, Patrick; Summers, David; Alhasso, Ammar; Carson, Alan; Stone, Jon
Abstract : Background: Studies have shown that around half of patients presenting with cauda equina syndrome (CES) have normal imaging, many of whom may have evidence of a functional neurological disorder. Results and Projects to Date: The Back or Leg Pain with Bladder symptoms study (BLB) study is a prospective case control study of all patients admitted with possible CES to the Western General Hospital, Edinburgh. We have recruited 101 patients (58 'scan negative' CES, 43 'scan positive' CES). A retrospective review of all patients presenting with possible CES to the Western General from August 2013-November 2014 demonstrated 287 referrals of which 197 patients had 'scan negative' CES. Rates of functional disorders and psychiatric comorbidity were higher in these patients than in patients with 'scan positive' CES (32% vs. 9%, 47% vs. 24%) and 53% of patients had chronic pain on follow up. A joint application with neurosurgery for a multi-centre audit of current treatment and incidence of CES was chosen by the British Neurosurgical Trainee Research Collaborative as their next project. Conclusions: Recruitment is above target for the main BLB project. Side projects bring supportive evidence of the higher rate of functional disorders in patients with scan negative Uro-Neurological disorders.